Life-history evolution: at the origins of metamorphosis - Holstein, Thomas W.; Laudet, Vincent (Current biology, 2014)
Metamorphosis is a widespread life history strategy of animals but apart from some model organisms it is poorly characterized. A recent study of moon jellies highlights the similarities and differences between the various types of metamorphosis and illuminates its molecular determinants.
Gesehen am 14.02.2017